2007
DOI: 10.1007/s00464-007-9541-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance differences in laparoscopic surgical skills between true high-definition and three-chip CCD video systems

Abstract: All the participants preferred HD to SD. High definition significantly improved laparoscopic knot tying, which requires precise depth perception, proving that HD is more than just a pretty picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…This result corresponds well with that of earlier studies, which showed that more movements were made to complete the tasks with the 2D system [9]. The fact that the error rate in the experienced group for task 1 had a tendency to increase on days 3 and 4 with the 2D system suggests that the participants in this group may have been driven by ''overconfidence,'' as noted previously by Hagiike et al [30]. However, there was no increase in the error rate with the 3D system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result corresponds well with that of earlier studies, which showed that more movements were made to complete the tasks with the 2D system [9]. The fact that the error rate in the experienced group for task 1 had a tendency to increase on days 3 and 4 with the 2D system suggests that the participants in this group may have been driven by ''overconfidence,'' as noted previously by Hagiike et al [30]. However, there was no increase in the error rate with the 3D system.…”
Section: Discussionsupporting
confidence: 92%
“…We expect that the new 3D system with full highdefinition quality will provide better 3D perception and accuracy of laparoscopic performance in the near future [30]. Moreover, this novel one-camera system, using the effect of difference in density, can be modified to simulate multiple cameras and can be conjoined with the ''multiview 3D monitor systems.''…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the image magnification by the newly available high-definition endoscopes facilitates the identification of laryngeal nerves and parathyroid glands, providing visual discrimination among different tissues and depths [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the introduction of modern high-definition laparoscopes, [15,16], their 3D visualization capability remains limited. Essentially a video imaging technique, they cannot show structures below the exposed surfaces.…”
Section: Discussionmentioning
confidence: 99%